Factors of stunting in toddlers (Analytical Study in the Work Area of the Tena Teke Health Center, Southwest Sumba, NTT) - Florensia Anjela Ina; Nabila Nur Azisah; Andi Alim; Erni Kadir (Lambung Mangkurat University, 2023)
Stunting is a nutritional problem that hurts the quality of life of children in achieving optimal growth and development according to their genetic or hereditary potential. This study aims to determine the relationship between mother's knowledge, food intake, and history of LBW with stunting in toddlers at the Tena Teke Health Center, Southwest Sumba Regency, NTT in 2022. This study used a survey method with a cross-sectional study design. A sample of 233 people was taken using a non-probability sampling technique (accidental sampling). Data were analyzed through editing, coding, tabulation, and data entry processes. Knowledge instruments were tested for validity and reliability, while instruments for food intake, history of LBW, and stunting were considered valid and reliable because they were standardized by the Indonesian Ministry of Health. The results showed that there was no relationship between maternal knowledge (p=0.504) and food intake (p=0.137) with the incidence of stunting in toddlers and there was a relationship between history of LBW and stunting in toddlers (p=0.000). This study concludes that there is no relationship between maternal knowledge and food intake with the incidence of stunting in toddlers and there is a relationship between a history of LBW and the incidence of stunting in toddlers. It is necessary to increase the mother's knowledge about nutrition during pregnancy to prevent LBW. Future studies should consider external factors that could influence the results of the study.